Coated metal roofing and cladding - Oliver, M. S. (Thomas Telford, 1997)
Based on investigations across Europe and North America, this report addresses the key areas of interest to architects engineers, manufacturers, installers, and building owners. Recommendations are given on the specification of appropriate materials, design guidance, installation, and maintenance, and on the need for training of installers.